Analysis of early use of everolimus with low-dose calcineurin inhibitors in kidney transplant recipient - I. G. Kim; N. A. Tomilina; I. V. Ostrovskaya; I. A. Skryabina; N. D. Fedorova (Вестник трансплантологии и искусственных органов, 2019)
Aim: to evaluate the efficacy and safety of early use of everolimus in combination with a reduced dose of calcineurin inhibitors (CNI) after kidney transplantation and define approaches to the selection and management of patients on everolimus-based therapy.Materials and methods. Sixty-seven kidney transplant recipients were included in the study, forty of them began taking everolimus from the first day after transplantation in combination with prednisolone and CNI, and twenty-seven patients were converted from mofetil mycophenolate to everolimus 2.9 ± 2.0 months after surgery, and their dose of CNI was reduced. The duration of follow-up was 51.2 ± 35.1 months. Four-years patient and uncensored by death graft survival rate were assessed regardless of the duration of everolimus use and was compared with the data in the control group of recipients (n = 89) who did not receive everolimus. The survival rate of the method of treatment with everolimus and the event-free graft survival were also evaluated. When calculating the survival rate of method of everolimus treatment, the event that required the discontinuation of the drug was taken as the ed-point. Events such as rejection, development or progression of renal dysfunction and proteinuria have been accepted as end-points in the calculation of event – free survival rate. The number of patients discharged from their surgical hospital and taken under the supervision of a nephrologist was adopted as 100%.Results. Patient and graft survival rate at 4 years after transplantation in the everolimus-based and control groups did not differ (p < 0.79 and p < 0.4, respectively). The 4-year survival rate of the method of everolimus treatment was 57.2%, and the event-free graft survival rate was 47.9%. The most frequent causes of everolimus withdrawal were rejection (25.8% of all causes), proteinuria (19%), progressive graft dysfunction (16, 1%) and adverse events (16.1%). The 4-year event-free graft survival depended on the initial kidney function and was significantly decreased (up to 32%) in the group of patients having the baseline Pcr >0.13 mmol/l in comparison with 59.3% in patients with normal baseline function, p < 0.04. The average level of Pcr Increased during the treatment from 0.14 ± 0.04 to 0.16 ± 0.09 mmol/l (p < 0.04), and the daily proteinuria increased from 0.18 ± 0.12 g/day to 0.66 ± 1.31 g/day (p < 0.004) by the end of follow-up.Conclusion. Everolimus with reduced dose CNI can be start from the first days or months after kidney transplantation. However, its applicability is limited to four years in almost 43% of patients due to rejection, progressive graft dysfunction, proteinuria and adverse events.